Evaluation of sperm functionality in non-human primates, focussing on sperm capacitation - Mabotha, Luke Allen (University of the Western Cape, 2019)
Magister Scientiae (Medical Bioscience) - MSc(MBS) === The incidence of male infertility is increasing, with up to 50% of infertile males having “unexplained” (idiopathic) infertility. Newly developed molecular techniques have great value in detecting subtle causes of male infertility, as compared to idiopathic infertility which may be explained by standardizing and optimizing sperm functional and structural tests in non-human primate (NHP) sperm. The aim of the study was to evaluate sperm functionality utilizing the sperm of two NHP species, i.e.1) the rhesus monkey (Macaca mulatta) and 2) the vervet monkey (Chlorocebus aethiops), and further evaluate the effect of physiological media (including commonly used, and newly formulated sperm wash and sperm capacitating media) on NHP sperm functionality. Sperm functionality was evaluated by investigating the following sperm functions i.e.: sperm motility, vitality, acrosome reaction (AR), hyperactivation, and mitochondrial membrane potential (MMP). Sperm functional tests included computer-aided semen analysis (CASA), motility analysis, BrightVit staining for sperm vitality, flourescenin isothiocyanate (FITC)- conjugated peanut agglutinin (PNA) staining for sperm acrosome integrity, induction of hyperactivation by stimulants (sperm preparation media containing capacitating ingredients), and mitochondrial inhibitor (Oligomycin-A) for testing MMP. All functional and structural tests were investigated in both species, except for acrosome integrity, mitochondrial inhibition and functional tests compared over time that could not be successfully completed and investigated in the rhesus species. Motility analysis tests proved that within the vervet species, the use of different physiological media results in statistically significant differences in motility and kinematic parameters over a 1 hour time period. Hyperactivation tests proved that capacitating physiological media produced significantly higher percentages hyperactivation when compared to sperm wash media within the vervet species over a 1 hour time period. Furthermore, within both NHP species, sperm structural analysis (vitality and acrosome integrity) results showed that no significant differences are present when making use of different physiological media over a period of 1 hour incubation. The incubation of vervet sperm with different concentrations of mitochondrial inhibitor, Oligomycin-A (0 μM, 5 μM, and 25 μM), resulted in motility inhibition over a 1 hour incubation period. By the evaluation of these tests it was found that the use of different sperm wash [Human tubal fluid (HTF), Ham‟s F-10® and HD Sperm Wash Plus (HDSWP)] and sperm capacitation media [Human tubal fluid with added caffeine (HTFC) and HD Sperm Capacitating Plus (HDSCP)] resulted in significantly different results within sperm functional tests as compared to sperm structural tests. The study indicates that the composition of media, varying from simple to more complex, used for semen preparation plays an important role in determining NHP sperm functionality. Based on these findings further investigation in larger NHP sample groups and human sperm are required to evaluate the role of certain ingredients in the development of more cost-effective media producing satisfactory results in terms of sperm functionality for artificial reproductive technologies (ART).